2013
DOI: 10.1089/gtmb.2013.0322
|View full text |Cite
|
Sign up to set email alerts
|

TERT Genetic Polymorphism rs2736100 Was Associated with Lung Cancer: A Meta-Analysis Based on 14,492 Subjects

Abstract: Background: Previous studies focused on the association of the telomerase reverse transcriptase (TERT) gene polymorphism rs2736100 with lung cancer did not reach the same conclusion. In the present study, we performed a meta-analysis to systematically summarize the possible association between TERT polymorphism rs2736100 and the risk for lung cancer. Method: We conducted a search of case-control studies on the association of TERT with susceptibility to lung cancer in PubMed, EMBASE, ISI Web of Science, Wanfang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…We found that TERT rs2736100 was still significantly associated with lung cancer when incorporated with many environmental and lifestyle factors. Overall, our data were consist with those from meta-analyses 38 - 40 , thus providing evidence that this locus is strongly associated with the development of the disease.…”
Section: Discussionsupporting
confidence: 75%
“…We found that TERT rs2736100 was still significantly associated with lung cancer when incorporated with many environmental and lifestyle factors. Overall, our data were consist with those from meta-analyses 38 - 40 , thus providing evidence that this locus is strongly associated with the development of the disease.…”
Section: Discussionsupporting
confidence: 75%
“…It has been thoroughly associated with lung cancer risk (mostly adenocarcinoma [ 242 , 249 ]), although there were also reports of no evident association [ 386 ]. Wang et al [ 387 ] and Yang et al [ 388 ] published meta-analyses in which they reported the association of rs2736100 with increased lung cancer risk (mainly adenocarcinoma) in both Caucasian and Asian populations. This SNP was identified to associate with an increased risk of myeloproliferative neoplasms (e.g., polycythaemia vera, essential thrombocythemia, and primary myelofibrosis) in Caucasian and Chinese populations [ 267 , 269 ].…”
Section: Telomere Maintenance Mechanismsmentioning
confidence: 99%
“…In particular, TERT polymorphisms are especially associated with ADC in never-smokers. Moreover, GWAS strongly suggest that both TERT and CLPTM1L polymorphisms actually modify the susceptibility to further develop a lung cancer (20)(21)(22)(23)(24).…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%